Economic Security of Households in the Region (Illustrated by the Ivanovo, Vladimir, Kostroma and Yaroslavl’ Regions) - I. I. Ledyaykina (Вестник Российского экономического университета имени Г. В. Плеханова)
Today when Russian economy is passing over to the market way of development, new objects are involved in trade and cash relations and the role of money is rising analysis of problems dealing with household economic security guarantee acquires extreme importance. It is defined as a situation, when conditions of living interest protection are secured, the system of social development and social protection of personality and family is guaranteed. The article provides the author’s classification of key elements of household economic security, threats to its different types are identified and the level of economic protection of households in the Ivanovo region and a number of adjoining regions (Vladimir, Kostroma, Yaroslavl’) is estimated on the basis of principle social indicators. Figures of human potential reproduction in Ivanovo, Vladimir, Kostroma, Yaroslavl’ regions were analyzed and compared with the average Russian and critical (threshold) values. The author underlined the active role of households in ensuring and strengthening their economic security. The key direction of their efforts today should become efficient management of their own economic security and investment into it. The article puts forward an idea to organize on mass media sites popularization of relevant economic behavior, where scientists and practical specialists in the field of economic security can take part.